2010
DOI: 10.1523/jneurosci.4384-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Refractory Period for Rejuvenating GABAergic Synaptic Transmission and Ocular Dominance Plasticity with Dark Exposure

Abstract: Dark exposure initiated in adulthood reactivates robust ocular dominance plasticity in the visual cortex. Here we show that a critical component of the response to dark exposure is the rejuvenation of inhibitory synaptic transmission, resulting in a decrease in functional inhibitory synaptic density, a decrease in paired-pulse depression, and a re-expression of endocannabinoid-dependent iLTD. Importantly, pharmacological acceleration of the maturation of inhibition in dark-exposed adults inhibits the re-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 37 publications
4
66
1
Order By: Relevance
“…In particular, changes in visual experience selectively altered mIPSC frequency in adult cortex during the refractory period for inhibitory synaptic plasticity [20]. Consistent with the refractory period notion, visual deprivation did not change eIPSCs or the density of inhibitory synaptic terminals.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In particular, changes in visual experience selectively altered mIPSC frequency in adult cortex during the refractory period for inhibitory synaptic plasticity [20]. Consistent with the refractory period notion, visual deprivation did not change eIPSCs or the density of inhibitory synaptic terminals.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we report that in adults visual experience specifically regulates inhibitory 'noise' (mIPSCs) without changing eIPSCs. In particular, visual experience reversibly regulates the frequency of mIPSCs, which is the only functional change in inhibitory synaptic transmission reported so far in adults during an age range previously referred to as the refractory period for plasticity [20]. Furthermore, we also found that non-genomic actions of oestrogen specifically alter mIPSC frequency in adult visual cortex, which suggests that this mechanism is a convergent locus for controlling inhibition in the adult brain.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Rapid inhibition is required to limit excessive excitation caused by Hebbian processes, but at present, we have evidence for rapid disinhibition that allows Hebbian and synaptic scaling processes to increase excitation [24,25]). One further complication arises from the finding that inhibitory changes may be restricted to early development and to the critical period in visual cortex [25,28,29]. However, a possible solution to this complication is that action potential-independent GABA release may be modulated by sensory experience and hence excitatory sensory drive in adult visual cortex [30].…”
Section: Inhibition Disinhibition and Homeostatic Mechanismsmentioning
confidence: 99%
“…Dark-exposure engages several mechanisms predicted to lower the threshold for synaptic plasticity in principle neurons (Cooper and Bear 2012). For example, dark exposure returns the NMDA subtype of glutamate receptor to the "juvenile" form, enhances the temporal summation of NMDAR-mediated synaptic currents and promotes re-expression of forms of synaptic plasticity typically limited to juveniles (Quinlan et al 1999;Yashiro et al 2005;Huang et al 2010;Montey and Quinlan 2011). In addition, dark exposure scales up excitatory synapses on principle neurons, increases visual cortex excitability, and expands the integration window for spike-timing dependent plasticity (Goel and Lee 2007;He et al 2007;Guo et al 2012).…”
mentioning
confidence: 99%